Work-Family Conflict Among Professional Women In The Construction Industry - Say, Xiao Mei (2020)
Most of the individuals experience conflict when trying to balance the roles between work and family. The conflict arises between work and family is known as work-family conflict. The increasing of women’s labour force participation and the number of dual-earner families have contributed to workfamily conflict. Prior research has focused mostly on the types of work-family conflict experienced by construction professionals. However, limited studies considered the causes and impacts of work-family conflict in the construction industry. Therefore, this research aims to investigate the causes and impacts of work-family conflict among professional women in the construction industry. The objectives are (1) to identify the causes of work-family conflict; (2) to examine the impacts of work-family conflict and (3) to study the strategies in reducing work-family conflict among professional women in the construction industry. The quantitative research method was used in this research and the data were collected through questionnaire survey. A sample of 104 professional women in the Klang Valley, Malaysia were used for this research. The findings revealed that both single and married respondents perceived work demands as the major contributor to the causes of work-family conflict. The single respondents perceived work-related outcomes as the most significant impacts of work-family conflict, whereas the married respondents perceived individual-related outcomes. The most effective strategies in reducing workfamily conflict was social support as perceived by both single and married respondents. This research also carried out inferential test and found out that there are significant differences between single and married professional women towards the causes, impacts and strategies of work-family conflict. The findings also revealed that there are significant association of working experience and working hours on the causes and impacts of work-family conflict. This research provides a framework for the exploration of workfamily conflict in the Malaysian construction industry. The present study also points to the need of construction companies in engaging the strategies for reducing work-family conflict to assist the employees in achieving workfamily balance.